Modern Solutions for Correction of Nasal Septum without Tamponade and their Disadvantages - Ergashevich, Qiyomov Ikhtiyor (Journal of Science in Medicine and Life, 2024)
Nasal diseases, which often significantly limit a person's quality of life, require careful diagnosis. To determine the causes of nasal congestion, rhinitis, snoring, sinusitis and headache, our doctors use the most modern examination methods: nasal endoscopy, pressure measurement, rhinomanometry, computer tomography, x-ray examination of the paranasal sinuses.